The relationship between father absence and hostility among Chinese depressed youths: A serial mediation model and the role of self-esteem and frustration tolerance - Liu, Xiao-Ge; Li, Yang; Xiong, Fang; Li, Wen-Tian; Liu, Lian-Zhong; John S., Sullivan (Frontiers in Pediatrics, 2023)
Background: While the association between father absence and youth hostility has been well-documented among depressed youths, there is a lack of research on the potential mechanism underlying such an association. This study aimed to test a serial mediation model of self-esteem and frustration tolerance on the link between father absence and youth hostility. Methods: A total of 137 Chinese youths with major depressive disorder were recruited from Wuhan Mental Health Center. They completed a survey including the Father Absence Questionnaire to measure father absence, the Chinese Hostility Inventory (CHI) to measure hostility, the Psychological Endurance Questionnaire to measure frustration tolerance, and the Self-esteem Scale (SES) to measure self-esteem. A series of multiple linear regression models were employed to assess the associations among father absence, self-esteem, frustration tolerance, and hostility. Results: Although father absence was modestly associated with hostility (r = 0.30, P<0.001), subsequent serial mediation analysis showed that father absence was not directly related to hostility (β=0.06, P=0.29) when self-esteem and frustration tolerance were included in the model. Higher levels of father absence had an adverse effect on levels of self-esteem, which decreased levels of frustration 32 tolerance, and thus higher levels of hostility among depressed youths. The indirect effects of father absence on hostility through self-esteem, frustration tolerance, as well as through self-esteem and frustration tolerance serially accounted for 28%, 24%, and 24% of the total effect, respectively. Conclusion: Our study tested a serial mediation model of self-esteem and frustration tolerance as mediators between father absence and hostility among depressed youths. The findings strengthened our understanding of the potential mechanism underlying the association between self-esteem and frustration tolerance, which may provide useful guidance for future intervention programs.